Epidemiological analysis of dengue’s one-year laboratory data in a tertiary care center in Western India - Adrejiya, Parth M.; Barve, Sonia; Nanda, Sandeep (International Journal Of Community Medicine And Public Health, 2023)
Background: Aedes aegypti and Aedes albopictus are the primary effective vectors for the dengue virus in India. The disease is conveyed through the bite of infected mosquitoes of the Aedes species and is the most quickly expanding vector-borne viral disease globally, putting an increasing number of locations at risk. Methods: We looked at the laboratory surveillance data and reported the percentage of dengue cases that were confirmed in the lab by month, location (urban vs. rural), and individual (age vs. gender) factors. Results: The maximum no. of suspected cases as well as found positive were in the monsoon and post-monsoon period from July to November. The dengue suspected cases were significantly more in the adult age group than in the pediatric age group. More cases were seen in urban areas than the rural areas. Conclusions: Serology confirmed positive dengue cases were maximum in the adult group residing in an urban area in the period of monsoon and post-monsoon period from July to November.